The Fate of the Jews in the Lazdijai District during the Nazi Occupation: from the Restriction of the Rights to Death - Brandišauskas, Valentinas (Genocidas ir rezistencija, 2008)
In the first days of the war, provisional committees were formed in the town of Lazdijai and at local councils of the district. They were not only concerned with everyday issues and organised the local civil administration and auxiliary police units, but also dealt with the “Jewish issue”.The partisan (insurgent) detachments maintained enforced public order, guarded state institutions and arrested former Soviet activists. There were Jews among them, but during the first days of the war they were arrested not as members of an ethnic minority, but for real or alleged activities during the Soviet occupation.In Lazdijai, the “Jewish issue” was considered at several conferences of civil servants of the district, with German military representatives also present. On 1 September 1941, a ghetto was established in the village of Katkiškės not far from Lazdijai, and the Jews from the town and the district were taken there. Mass arrests of the Jews which had started in August ended in September when they were taken to the ghetto.
Keywords: German occupation; collaborants; Holokaust; Lazdijai district